Looted Libraries, Looted Books : The Swedish Case - Sjökvist, Peter (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
Supported by the legal ideas of Hugo Grotius, the Swedish armies exploited opportunities to seize books as spoils of war from conquered enemies to an unparalleled degree in the seventeenth century. They took books from countries such as today's Latvia, Poland, Germany, the Czech Republic and Denmark, distributing the goods to recently founded institutions and private manors in their native country. In Looted Libraries, Looted Books - The Swedish Case, Peter Sjökvist gives a summarizing overview of these plunders: from which regions and owners full libraries or selected books were taken during the conflicts, where they subsequently tended to end up when arriving in Sweden, and how they have been received and curated over the years. It is argued that it can be questioned whether large portions of the spoils have served any proper user needs in their new contexts.